Rio, 40 Graus: sua censura e os patamares de uma conscientização cinematográfica - Silva, Cleonice Elias da (2015)
This research aimed to analyze the film Rio, 40 Degrees (Nelson Pereira dos Santos, 1955) and the mobilization occurring between Brazilian intellectuals after censorship by the colonel and chief of police Geraldo Menezes Cortes. To study this mobilization we analyze texts published in the Brazilian press in the second half of 1955. The sources of this research correspond to the film and the press articles published in that period. An important guiding principle for reflection that we present are the questions raised by Marcelo Ridenti (2000, 2010) about the appreciation of the people in the Brazilian culture and the revolutionary brazilianness. We propose a new analytical bias to think the film as historical and aesthetic document, this bias concerns the aesthetic and ideological project of national-popular. In the case of mobilization that emerged after the censorship of the film, we stated that it gave discussions on film production in Brazil, touting the issues surrounding the early '50s Cinema Congress, the main one, the defense of national cinema. However, the proportions assumed by the mobilization in support of the release of the film, printed a new dynamic in discussions of the Cinema Congress